The effects of carbohydrate ingestion on 20 kilometer cycle time-trial performance - Hawley, J. A.; Palmer, G. S.; Burke, L. M.; Clancy, M. C.; Noakes, T. D (Medicine & Science in Sports & Exercise, 1998)
Well-trained cyclists (N = 14) ingested 8 ml/kg of CHO or a placebo beverages 10 minutes before an exercise test that featured a 20 km time-trial. There was no difference between performance, heart rate, or mean power output between the two trials. It was concluded that ingestion of CHO immediately before to 30 minutes of high intensity cycling does not improve performance. Implication. Last minute CHO ingestion does not improve performance in 30-minute high intensity tasks.